Softening characteristics of wet wood under quasi static loading - Hamdan, S.; Dwianto, W.; Morooka, T.; Norimoto, M. (Walter de Gruyter GmbH, 2000)
In order to examine the possible influences of temperature on the wood constituents, two groups of wood species namely softwood (needle leaf wood) and hardwood (broad leaf wood) were subjected to heat or steam treatment during large radial compression between 0°C and 200°C. Two well-defined softening regions are observed. Both species showed the glass transition Tg of lignin at ∼90°C and ∼60°C for softwood and hardwood respectively and a second transition region at ∼ 160°C. The softening behavior between the first and second transition in softwood is in contrast with the softening behavior of hardwood. This difference reflects the difference in the distribution of the relaxation process due to lignin, which suggests the difference in chemical structure of lignin between softwood and hardwood.